2008
DOI: 10.1111/j.1365-2648.2008.04628.x
|View full text |Cite
|
Sign up to set email alerts
|

A unique practice model for Nurse Practitioners in long‐term care homes

Abstract: Practice models designed to meet the distinctive needs of LTC homes and residents can enhance quality of care, even with low NP:resident ratios. Participation of key stakeholders in the identification of care priorities and planning contributed to the success of this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 21 publications
4
35
0
Order By: Relevance
“…The majority of participants emphasized the value of the NP in helping to avoid unnecessary hospitalization, a finding confirmed in previous quantitative research [2,13-15]. Participants emphasized how not only were cost savings important, but so too was saving residents and their usually older family members from physical and emotional strain of unnecessary trips to the hospital.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The majority of participants emphasized the value of the NP in helping to avoid unnecessary hospitalization, a finding confirmed in previous quantitative research [2,13-15]. Participants emphasized how not only were cost savings important, but so too was saving residents and their usually older family members from physical and emotional strain of unnecessary trips to the hospital.…”
Section: Discussionsupporting
confidence: 57%
“…Nurse practitioners (NPs) have provided services in some long term care (LTC) homes in the Unites States since the 1970s [1], in Canada since 2000 [2,3], and only recently in the United Kingdom [4]. This trend has helped address critical issues in LTC homes such as the increasing proportion of older residents with complex health problems, limited physician services, inadequate quality of care, and escalating healthcare costs [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The NPs delivering a nursing model of care situated within the HA service was instrumental in upskilling ACF staff (nursing and allied health) facilitating their confidence and ability to work to fulfil their scope of practice which in turn positively impacted on workplace satisfaction. Enhanced staff clinical confidence promoted earlier assessment and referral to the NP and ultimately HA, an observation reflected in other studies that report fewer hospital admissions when ACFs employ an NP [50]. …”
Section: Discussionmentioning
confidence: 96%
“…[23,25,[32][33][34] However, the majority of studies to date examining the utility of an EPHR have been done in outpatient settings where there is often a complete absence of the type of nursing care plans required within acute and LTC environments. Unlike within an outpatient setting, within a LTC setting nurses assume a significant portion of the direct care requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike within an outpatient setting, within a LTC setting nurses assume a significant portion of the direct care requirements. [32] It is possible that this finding may be specific to LTC only and may be linked to the increased role that nurses and particularly nurse practitioners assume over the clinical care of patients, [33] however given the paucity of research it is difficult to discern. Consistent with the current study findings, Thede (2009) identified that caregivers require very specific consideration when the elements of an EPHR are being constructed and indicated that nurses should play a very significant role in any EPHR development.…”
Section: Discussionmentioning
confidence: 99%